THE INFLUENCE COMMUNICATIVE APPROACH BETWEEN MASTERY VOCABULARY AND STUDENTS’ READING SKILL - Totoh Tauhidin Abas (Universitas Singaperbangsa Karawang, 2017)
This paper explain about communicative approach between Mastery Vocabulary and Students’ Reading Skill. The aim of the research to prove the students must following this English practical lesson is easy, directly, spontaneous, happy, and fun and its can be English life skill. The teacher must mastery vocabulary well and give good example advice to learn by heart each vocabulary and use it in daily activity. The teacher should ensure that influence communicative is tired, just important thing don’t be shy, doubt, nervous its must be brave to do it. Give nice and fresh atmosphere in the classroom, it does not easy boring they will enjoyable in unlimited time. In order this program well we gave the greatest spirit, reward and punishment. This activity have made by children as like as daily activity or life skill . So much reading many kind of difference material in English they can easily to translate directly and spontaneous and its can help communicative with others.